Earth-abundant transition-metal-based bifunctional catalysts for overall electrochemical water splitting: A review - Wang, Jiajia; Yue, Xiyan; Yang, Yanyan; Sirisomboonchai, Suchada; Wang, Peifen; Ma, Xuli; Abudula, Abuliti; Guan, Guoqing (Journal of Alloys and Compounds, 2020)
Production of hydrogen by electrochemical water splitting is considered as one of the most promising ways for sustainable energy storage and hydrogen society realization in the future. However, the key for the large-scale application of this technique is to develop highly efficient electrocatalysts with low-cost to replace the noble-metal-based ones. To date, a series of transition-metal-based bifunctional electrocatalysts for both anode and cathode have been already developed for the overall water splitting. Herein, the characteristics of hydrogen and oxygen evolution reactions on the electrodes of water electrolysis cell and the basic methods for the evaluation of the performance of electrocatalysts are introduced at first and then, the prospects of various earth-abundant transition-metal-based bifunctional electrocatalysts are critically reviewed. Finally, the challenges in the development of earth-abundant transition-metal-based bifunctional electrocatalysts are discussed. It is expected to provide a guidance for the design and fabrication of the novel bifunctional electrocatalysts with high performance in a practical water splitting process. [Display omitted] •Mechanisms on HER and OER on the cathode and anode of water electrolysis cell are summarized.•Evaluation parameters for electrochemical water splitting are systematically reviewed.•Various transition-metal-based bifunctional electrocatalysts are analyzed and discussed.•Challenges for the development of transition-metal-based bifunctional electrocatalysts are presented.•Outlook on design and construction of bifunctional electrocatalysts in a practical water splitting process is given.